Front és hátország a szegedi k.u.k. 46.-osok kapcsán hivatalos propaganda és a privát szféra - Tóth István; A Nagy Háború hatása a mindennapok kultúrájának változására (2015) (Szeged) (2018)
The article emphasizes the fact that the warfront and the events occurring there during the war affected relations at the hinterlands directly. The continuous need to supply the warfront with manpower resulted in a more prominent role for women in production in the hinterlands. Therefore, juvenile delinquency became a major issue. The majority of schools have temporarily been converted to military hospitals. This was a less discussed topic of propaganda. They rather focused on reporting exclusively optimistic news regarding the situation on the front. Censorship had a strong, daily presence in the press. The article publishes various almost trivializing articles from both the Western and Eastern fronts, respectively, emphasizing the fulfilment of the central power’s will. They, however, neglected to discuss heroic dead, numbering in the hundreds of thousands. Only those POW-related articles were published that emphasized the well-being of these prisoners of war. In order to support the topic, artistic painting and contemporary photographs depicting the warfront and the hinterlands are published in the final part of the article.
Keywords: Bölcsészettudományok; Történettudomány és régészet